1999
DOI: 10.1002/(sici)1096-9861(19990428)407:1<1::aid-cne1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional synapses are formed between human NTera2 (NT2N, hNT) neurons grown on astrocytes

Abstract: The formation of functional synapses is a late milestone of neuronal differentiation. The establishment of functional synapses can be used to assess neuronal characteristics of different cell lines. In the present study, we examined the in vitro conditions that influence the ability of human neurons derived from the NT2 cell line (NT2N neurons) to establish synapses. The morphologic, immunologic, and electrophysiologic characteristics of these synapses was examined. In the absence of astrocytes, NT2N neurons r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 46 publications
(49 reference statements)
6
105
1
1
Order By: Relevance
“…An astrocyte-induced increase in synaptogenesis has been reported in different culture preparations, including neuronal cell lines [24], hippocampal neurons derived from stem cells of adult rats [25,26], and neurons from spinal cord [27], cortex [28], hippocampus [28,29] and hypothalamus [28] of embryonic or perinatal rats. In all of these cases, however, it cannot be excluded that astrocytes increased synapse numbers indirectly by enhancing neuronal survival or axonal and dendritic growth.…”
Section: Astrocytes Control Synapse Numbermentioning
confidence: 99%
“…An astrocyte-induced increase in synaptogenesis has been reported in different culture preparations, including neuronal cell lines [24], hippocampal neurons derived from stem cells of adult rats [25,26], and neurons from spinal cord [27], cortex [28], hippocampus [28,29] and hypothalamus [28] of embryonic or perinatal rats. In all of these cases, however, it cannot be excluded that astrocytes increased synapse numbers indirectly by enhancing neuronal survival or axonal and dendritic growth.…”
Section: Astrocytes Control Synapse Numbermentioning
confidence: 99%
“…[14][15][16][17] NT2.N cells have been found to generate action potentials on depolarization. 18,19 In addition, they also express the high-voltage-activated calcium channels, pharmacologically classified as L, N, P/Q, and R, 20 as well as calcium-activated BK channels, which are involved in neuronal hyperpolarisation after action potential firing. 21 We have recently demonstrated that NT2.D1 cell-derived neuron and astrocyte (NT2.N/A) networks can communicate and so have the potential to interact with each other as observed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…13 Treatment with RA and mitotic inhibitors for several weeks ultimately results in the production of postmitotic, neuron-like cells (NT2N), 13,14 which express neurotransmitters, 15 functional glutamate receptors, 16 calcium channels, 17 mature neurofilament and cytoskeletal proteins, 18 and other proteins indicative of secretory activity and synaptogenesis. 14,19 They fail to acquire a fully mature phenotype in culture and terminally differentiate only when transplanted to the animal brain. 20 Grafted NT2N cells to the brains of adult nude mice show evidence for terminal differentiation by 6-8 weeks and elaborate processes within 3 weeks.…”
Section: Nt2 Neuron Cell Trialsmentioning
confidence: 99%
“…It has been shown, for example, that coculture of NT2N cells with astrocytes substantially prolongs survival and enhances maturation and synaptogenesis in vitro compared with NTN2 cultures alone. 19,22 Phase 1. Five years ago, a clinical trial began to assess the safety of intrastriatal NT2N (produced by Layton Bioscience, Inc. and known as LBS neurons for human use) transplantation in patients with basal ganglia infarcts and stable motor deficits 6 months to 6 years before implantation.…”
Section: Nt2 Neuron Cell Trialsmentioning
confidence: 99%